Effect of liver biopsy size on MASLD fibrosis assessment by second-harmonic generation/two-photon excitation fluorescence microscopy - Daniel T. Field; Yayun Ren; Kutbuddin Akbary; Elaine Chng; Dean Tai; Nikolai V. Naoumov; David E. Kleiner; Jonathan A. Fallowfield; Timothy J. Kendall; Arun J. Sanyal (JHEP Reports, 2025)
Background & Aims: Fibrosis in metabolic dysfunction-associated steatotic liver disease (MASLD) is a prognostic indicator and clinical trial efficacy endpoint. Second-harmonic generation/two-photon excitation fluorescence (SHG/TPEF) microscopy images unstained tissue sections and, when integrated with artificial intelligence models, generates a continuous fibrosis value (qFibrosis) and ordinal qFibrosis stage. The impact of biopsy size and location on the accuracy of these approaches has not been assessed in MASLD, leaving quality assurance procedures undefined. Methods: One unstained section each from 100 hepatectomy/explant MASLD cases, 20 of each pathologist-assigned Non-alcoholic Steatohepatitis Clinical Research Network (NASH-CRN) fibrosis stage (F0–F4), were used to create virtual core biopsies by cropping regions from within the whole parent section. Regions varied in length (5–30 mm) with a fixed width of 0.9 mm, width (0.5–1.3 mm) with a fixed length of 15 mm, or position within the whole parent section. SHG/TPEF was used, and the qFibrosis continuous value and stage of the virtual core biopsies were determined for comparison with those of the whole parent section. Results: The qFibrosis continuous value and stage correlated strongly with pathologist-assigned NASH-CRN stage (rs = 0.92). Increasing the length and width of virtual biopsies increased the correlation between the qFibrosis continuous value and the agreement with the qFibrosis stage of the whole parent section, stabilising between 20–26 mm in length and 0.9 mm in width. The position within the tissue did not influence qFibrosis metrics. Conclusions: Longer (>20 mm) and wider (>0.9 mm) biopsies provide more accurate fibrosis assessment using SHG/TPEF. Biopsy position and orientation do not influence accuracy. Impact and implications: Fibrosis assessment is an important prognostic indicator and clinical trial endpoint in metabolic dysfunction-associated steatotic liver disease, but liver biopsy sampling variation quality assurance has not been investigated for second-harmonic generation/two-photon excitation fluorescence (SHG/TPEF) microscopy quantification of fibrosis. Longer (>20 mm) and wider (>0.9 mm) biopsies allow for more accurate digital assessment of fibrosis. Clinical trials should incorporate suitable protocols to verify biopsy sizes that optimise digital fibrosis assessment using SHG/TPEF.